Pesticides an international code of conduct - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
An international code of conduct for the distribution and use of pesticides was approved at the 23rd Conference of the United Nations Food and Agriculture Organization (FAO) and adopted unanimously by the 158 member states. It took three years to...